Analisis Pemanfaatan Online Public Access Catalog (OPAC) Sebagai Alat Temu Balik Informasi Bagi Pemustaka Di Perpustakaan Umum Kota Bukittinggi - Winda Septrina; Rika Jufriazia Manita (Politik Islam, 2022)
The problem studied in this research is the use of the Online Public Access Catalog (OPAC) as a tool for information retrieval for visitors at the Bukitinggi City Public Library. The purpose of this study is to identify the use of OPAC as an information retrieval tool and to find out the obstacles faced by users in using OPAC and efforts to overcome obstacles when searching for information using OPAC at the Bukittinggi City Public Library. The research method used is descriptive research with a qualitative approach. Data collection techniques that the author uses are observation, interviews and documentation. Data analysis techniques in this study begin with data reduction techniques, data presentation, and conclusion drawing or data verification. The results of the research that the authors found that the use of OPAC as an information search tool has not been used optimally, instead of using OPAC as a means of information retrieval, users tend to go directly to the bookshelf to browse the books they need. This is due to the lack of user understanding in using OPAC as an information retrieval tool. This statement shows that the┬áOPAC service at the Bukittinggi City Public Library is not good, because there are obstacles faced by users, namely internal and external constraints, such as the lack of socialization of the library to library visitors. The availability of computers as a means to search for information is still lacking and there is no manual or manual for using the Online Public Access Catalog (OPAC).